Hematological parameters for a single oral intake of sodium iodide (Na131I) to the body of experimental rats - T. V. Tsyganok; N. K. Rodionova; I. P. Drozd; L. V. Tarasenko; V. I. Fedorchenko (Ядерна фізика та енергетика)
Study of hematological parameters (number of erythrocytes, leukocytes and leukogram) of peripheral blood of laboratory Wistar rats after administration of single oral radionuclide 131I in a solution of sodium iodide (Na131I) with activities of 3.3, 19.16, 113.8 and 327.0 kBq per animal was performed. Number of red blood cells in the bloodstream throughout the observation period was not significantly changed. Number of white blood cell count increased. The increase of activity injected by radioiodine caused reliably greater degree of significant increase in the number of leukocytes throughout the experiment due to increase of the absolute number of lymphocytes.